2014
DOI: 10.1007/978-3-319-01499-9
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis with Supported Size-selected Pt Clusters

Abstract: Under ultra high vacuum conditions the electronic structure, adsorption properties and reactivity of two olefins on surfaces and Pt clusters were probed in the submonolayer range. With adsorbed trichloroethene a possible cluster-adsorbate induced change in the electronic structure and for ethene a low temperature, size dependent self-/hydrogenation was observed.In a collaborative approach, the Pt clusters were investigated under ambient pressure conditions. The clusters were characterized on local and integral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 262 publications
(660 reference statements)
1
11
0
Order By: Relevance
“…The single Pt atoms are now the most catalytically active, outnumbering the larger Pt n >35 clusters by a factor of 17 and the Pt n >1 cluster by over a factor of 2, per atom. For the larger sample Pt n >35 , not all atoms are exposed to the surface; i.e., a dispersion of about 60–70% has to be considered . Thus, the observed activity per exposed atom is slightly less than twice the value shown in Figure b, however, still well below that of single atoms and Pt n >1 clusters.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The single Pt atoms are now the most catalytically active, outnumbering the larger Pt n >35 clusters by a factor of 17 and the Pt n >1 cluster by over a factor of 2, per atom. For the larger sample Pt n >35 , not all atoms are exposed to the surface; i.e., a dispersion of about 60–70% has to be considered . Thus, the observed activity per exposed atom is slightly less than twice the value shown in Figure b, however, still well below that of single atoms and Pt n >1 clusters.…”
Section: Resultsmentioning
confidence: 85%
“…The clusters were deposited on the wafer samples (350 μm thickness, thermally oxidized with an oxide of 50 nm thickness) and Si TEM grids (see details below) using a high frequency laser ablation cluster source and a transfer chamber, described in detail elsewhere. ,, In brief, the beam of a diode pumped Nd:YAG laser (DPSS Spitlite, 100 Hz, 70 mJ at 532 nm; InnoLas, Germany) was focused onto a rotating (1 Hz) metal target disk (99.99% Pt, Goodfellow, USA). Cooling of the resulting plasma was achieved via a delayed helium (He 6.0, Westfalen, Germany) gas pulse and an adiabatic expansion of the helium–platinum vapor through a nozzle into the vacuum.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The size distribution is then determined by the settings of the cluster source [22]. Recent TEM studies on Pt have shown that the particle area distribution of a sample deposited with these settings can be fitted by a log-normal distribution [23,24,25] and approximately correspond to the size distribution from the source. In these studies a particle size distribution of 1-1.5 nm was determined and this is the expected size range studied in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…This requirement seems to conflict with the need of increasing the surface area of the active catalyst in order to maximize the reactivity. To cope with these requirements, many attempts have been made to produce subnanometer‐sized‐supported Pt clusters and some results about the effective catalytic reactivities have been reported . For the specific case of CO oxidation to produce harmless CO 2 , Heiz and co‐workers reported reactivities for size‐selected nanoclusters composed of a number of Pt atoms going from eight to twenty .…”
Section: Introductionmentioning
confidence: 99%